Visit of Prime Minister Dr. Manmohan Singh to Brazil and Cuba, September 10-18, 2006 [First IBSA Summit & XIV NAM Summit]. - Manmohan Singh 1932-; India. Ministry of External Affairs. Public Diplomacy Division; India-Brazil-South Africa Dialogue Forum. Summit Meeting 2006 Brazil).; Conference of Heads of State or Government of Non-aligned Countries 2006 Havana, Cuba). (New Delhi Public Diplomacy Division, Ministry of External Affairs, Government of India, 2006)
Addresses of Indian prime minister on diplomatic and trade relations delivered during his visit to Brazil and Cuba; includes his addresses at First IBSA Summit & XIV NAM Summit.
Keywords: Manmohan Singh -- 1932- -- Travel -- Brazil; Manmohan Singh -- 1932- -- Travel -- Cuba; Visits of state -- Brazil; Visits of state -- Cuba; India -- Relations -- Brazil; India -- Relations -- Cuba; Brazil -- Relations -- India; Cuba -- Relations -- India